Penerapan Ajaran Kausalitas Atas Kasus Pembunuhan “Kopi Sianida” Dengan Terdakwa Jessica Kumala Wongso - Syarlis, Syarlis (Varied Knowledge Journal, 2024)
In determining the causal relationship between actions and the resulting consequences, criminal law uses certain measures or criteria to determine the causal relationship between actions and the resulting consequences. This is where the teaching of causality is important, in seeing the relationship between one action and another which causes prohibited consequences. Based on the results of the analysis, it shows that the role of the Judge in making decisions is associated with the teaching of causality, namely the use of logic and legal reasoning in linking a series of events with the evidence and fatka - the facts presented. Consolidating/finding a series of events, namely seeing, admitting and confirming that a criminal act has occurred. In decision number 777/Pid.B/2016/PN.JKT.PST, the judge's role in decision making is linked to the teaching of causality, namely the use of logic and legal reasoning in linking a series of events with the evidence and facts presented.